Analysis of Production Cost Using the Full Costing Approach and Determining Selling Prices Using the Cost Plus Pricing Method at Ali Batagor - Khairida Nur Rahmah; Nurwani Nurwani; Laylan Syafina (Indonesian Journal of Islamic Economics and Finance, 2026)
This study aims to analyze the selling price determination of Ali Batagor's business in Medan City using traditional methods, Full Costing, and Cost Plus Pricing. Using a descriptive qualitative case study approach, data were collected through interviews, observations, and documentation spanning a 30-day observation period to ensure data representativeness and minimize daily fluctuation bias. The revised application of the Full Costing method incorporating direct raw materials, imputed direct labor costs (BTKL) based on Medan's regional minimum wage (UMR), and fixed overhead through straight-line asset depreciation yields a more accurate Cost of Goods Sold (HPP) of Rp5,908 per portion (total daily production cost: Rp590,795 for 100 portions). This reveals that the current selling price of Rp5,000 per portion actually results in a daily operating loss of approximately Rp90,795 a condition of severe undercosting invisible to the owner under traditional pricing. Using the Cost Plus Pricing method with a 30% profit margin, the scientifically justified selling price is Rp7,680 per portion. A demand sensitivity analysis suggests that even a moderate price increase to Rp6,000–Rp7,000, combined with value bundling strategies, can move the business from structural loss into profitability without proportionally sacrificing sales volume. This study demonstrates that the integration of Full Costing and Cost Plus Pricing is critical for MSME financial sustainability, and that the most urgent managerial implication for culinary MSMEs is the recognition and quantification of non-cash costs.